Comparative study of divided attention and reaction time among the players of Baghdad volleyball clubs - Abdulhadi, Zaman Saleh; Saad, Ahmed Khattar; Abed , Mohammed Ibadi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this paper was to identify the differences in the level of divided attention and reaction time among volleyball players according to their specializations. The present study was conducted on volleyball players of Baghdad, who participated in the elite volleyball league in the 2012/2013 season. The study was completed within the time frame of March 2013 to May 2013 in the Center for Educational Studies and Psychological Research of the University of Baghdad. A total of 24 players were present in the research community. Participants were selected in a deliberate way. Most of the participants had participated at national level games. The statistical analyses were conducted using the Statistical Package for the Social Sciences (SPSS). Based on the findings of the study, the researchers concluded that a statistically non-significant difference was found in the volleyball players according to their specializations in the divided attention variable, and a statistically significant difference was found in the volleyball players according to their specializations in the reaction time variable.